Peningkatan Digitalisasi Dalam Pelayanan Publik Melalui Aplikasi A’kio di Kantor Bupati Gowa - Ridwan; Apriliya, Dela; Pratidina, Nur Ainun; Rante Allo, Imel Kristi (Jurnal Pengabdian Masyarakat, 2025)
Public services are the government's main task in meeting the basic and general needs of society. In the era of digitalization, the Gowa Regency Government has implemented the A'kio e-Disposition application as an innovation to increase efficiency and transparency in public services. This research aims to analyze the effectiveness of the application, highlighting its ease of use, the reliability of its technology, and its influence on the quality of mail administration. The research method involves observation, practical application use, and performance evaluation. The research results show that A'kio e-Disposition is able to speed up the letter management process, increase accuracy, and support technology-based government management. However, aspects of data security and technological infrastructure capacity still require further development. Overall, this application is an example of effective digitalization of public services in realizing responsive, transparent and accountable government.